P1480French experience of SICD implantation. (18th June 2020) - Proukhnitzky, J; Badenco, N; Gandjbakhch, E; Maupain, C; Waintraub, X; Duthoit, G; Hidden-Lucet, F; Marijon, E
Abstract: OnBehalf: GPUR Introduction: The subcutaneous ICD prevents complications of transvenous leads. Its implantation needs a defibrillation test. Performing this test increases the time of procedures.. Purpose: The aim of our study is to describe the experience of subcutaneous ICD of Assitance Publique des Hopitaux de Paris (AP-HP). Materials and Methods: In a retrospective cohort we included patients who were involved in subcutaneous ICD treatment at the 5 hospitals of AP-HP from December 2012 to April 2018.Analysis used the Kaplan-Meier method and the Mann-Whitney U test. Results: 162 patients were implanted. 76% of implantations were for secondary prevention before 2017, but only 49% after 2017. 126 (77%) tests were successful at first shock, 14 (8.6%) needed a second shock or more, 9 (5.5%) did not have a test. The shock impedance was significantly higher when the shock was not effective at the first test, 82 ohms CI 95% [68; 112] versus 66 ohms CI 95% [64; 70], p <0.05. 6 patients died (3.7%). Late follow up showed 23 (10%) appropriate shocks and 24 inappropriate shocks (11%) mainly due to T wave oversensing (37.5%). Conclusions: This is the first french experience of SICD implantation. Success of defibrillation test was lower than expected.